توظيف المدخل الاتِّصالي الثَّقافي في تصميم وحدات دراسيَّة للنَّاطقين بغير العربية - Al-Turk, Reem Adel Sabel; Chik, Abdul Rahman; Md Ghalib, Mohd. Feham (2015)
Using cultural communicative approach in designing lesson units for non Arabic speakers